Avaliação do uso da terra em micro̧bacia utilizando uma matriz de partição fuzzy - Campos, Sérgio [UNESP]; Piroli, Edson Luís [UNESP]; Zimback, Célia Regina Lopes [UNESP]; Rodrigues, João Batista Tolentino [UNESP] (My University, 2007)
Informatics evolution presently offers the possibility of new technique and methodology development for studies in all human knowledge areas. In addition, the present personal computer capacity of handling a large volume of data makes the creation and application of new analysis tools easy. This paper aimed the application of a fuzzy partition matrix to analyze data obtained from the Landsat 5 TMN sensor, in order to elaborate the supervised classification of land use in Arroio das Pombas microbasin in Botucatu, SP, Brazil. It was possible that one single training area present input in more than one covering class due to weight attribution at the signature creation moment. A change in the classification result was also observed when compared to maximum likelihood classification, mainly when related to bigger uniformity and better class edges classification.
Analysis of soil use in a microbasin using a fuzzy partition matrix
Keywords: Fuzzy partition matrix; Satellite image; Supervised classification; Data reduction; Fuzzy systems; Land use; Maximum likelihood; Personal computing; Satellite imagery; Soils; fuzzy mathematics; image analysis; land use; Landsat thematic mapper; maximum likelihood analysis; satellite data; Botucatu; Brazil; Sao Paulo [Brazil]; South America